Environmental Security from the Perspective of Protecting Public Order - Megarin, Youcef (Journal of Legal Studies and Researches, 2023)
The constitutional establishment of environmental security from the perspective of protecting public order is a contemporary approach that would protect security and national unity, and basis the Algerian constitutional founder implicitly recognized this approach, according to Article: 21, whose dimensions we noticed were insufficient to address the requirements of public security in light of the current circumstances.